Pulsed light: Innovative non-thermal technology for preservation of fruits and vegetables - Roji Waghmare; Manoj Kumar; Baohong Zhang; Rahul Yadav; Ajinath Dukare; Radha; Deepak Chandran; Pratik Nayi; Muzaffar Hasan; Sangram Dhumal; Trupti Dharmarao; Tanu Malik; et al. (Food Physics)
Pulsed light (PL), a relatively new non-thermal technology can be used as a possible substitute to the conventional (thermal and chemical) technology for disinfecting a wide variety of fruits and vegetables. The short-duration light pulses, ranging from 1 to 20 flashes per second with an energy density of about 0.01–50 Jcm−2, ensure the killing of several disease-causing microorganisms by causing minimal impact on the quality parameters in fruits and vegetables. This technology enhances safety and extends shelf-life period of fruits and vegetables. Furthermore, PL decreases or inhibits the harmful effect of conventional techniques on nutritional components. The review discusses recent research on PL's influence on nutritional and physicochemical parameters and its potential applications for extending the shelf life of fruits and vegetables. This PL technology can be successfully employed alone or in combination with other techniques for enhancing fresh produce life. PL is considered a safe, eco-friendly and non-thermal technique for shelf-life extension. For this review article, keywords such as pulsed light, fruits and vegetables, microbial safety and shelf life were selected and most relevant papers were cited. Thus, the present review article, supported by 70 references, highlights the novel potential of PL treatment and its diverse applications in the fruit and vegetable sector.